Pasteurella multocida epiglottitis: A case report - Laura Sofoulis; Blake Dawson; Tuan Pham (JEM Reports)
Background: Acute epiglottitis is a life-threatening condition usually caused by streptococcal or staphylococcal species. It is rarely caused by Pasteurella multocida, which is an oropharyngeal commensal in cats and dogs, and is usually responsible for human skin infections following inoculation by bite or scratch. Case report: We report a case of a 50-year-old female who presented to the emergency department with acute epiglottitis due to Pasteurella multocida. The patient suffered rapid deterioration and subsequent hypoxic cardiac arrest requiring advanced life support measures and intubation. She recovered well following a course of penicillin-based intravenous antibiotics and airway support in the intensive care unit. Infection was likely acquired after close contact with her pet dog. Why an emergency physician should be aware of this: Pasteurella multocida can cause a variety of atypical infections, including acute epiglottitis, and should be considered a possible causal organism in those with a history of animal exposure. While it is important to take a careful exposure history, the nature of a patient's presentation may necessitate a reliance on collateral history when there is unexpected and rapid patient deterioration. As is demonstrated in this case, the diagnosis, management, and treatment of adult-onset epiglottitis is multidisciplinary in nature and reliant on careful patient assessment that correlates pertinent historical findings with relevant laboratory results.